Whole-genome sequencing of acral melanoma reveals genomic complexity and diversity - Felicity Newell; James S. Wilmott; Peter A. Johansson; Katia Nones; Venkateswar Addala; Pamela Mukhopadhyay; Natasa Broit; Carol M. Amato; Robert Van Gulick; Stephen H. Kazakoff; Ann-Marie Patch; Lambros T. Koufariotis; et al. (Nature Communications, 2020)
Acral melanoma occurs on the soles of the feet, palms of the hands and in nail beds. Here, the authors reports the genomic landscape of 87 acral melanomas and find that some tumors harbor a UV signature and that the tumors are diverse at the levels of mutational signatures, structural aberrations and copy number signatures.